Direito de propriedade e justiça distributiva no Brasil: ampliação das capacidades como forma de combater a pobreza rural - SÁ, João Daniel Macedo (Universidade Federal do Pará, 2017)
This work discusses property rights relations from the modern notion of distributive justice. It analyzes the extent to which rural private property constitutionally defined favors a notion of distributive justice compatible with the foundations of the democratic State based on the rule of law. It is based on egalitarian liberal thinking of John Rawls, to defend the role of justice in preserving the freedom of the individual, while considering that the value of dignity implies equal access to political, social, and, to some extent, of economic goods, that should be ensured mainly by the state. It is argued that in a just society, everyone should receive equal share of the benefits that society provides and of the costs that it requires. Supporting this idea, it is also based on Amartya Sen thoughts to argue that property right is intrinsically important, but also instrumentally valuable to enable individuals to achieve development. Further, the thesis argues that the classical liberal notion of property-liberty, which generates the absolute and exclusive power over the thing, and the social notion of property-duty, based on social function, converges on the notion of property-capacity, whose focus is on promoting real freedom of choice for individuals. The work will demonstrate that the State must, in order to fight rural poverty, and for the sake of justice, ensure more equitable access to ownership rights of rural lands in the country. It presents, based on government statistics, a criticism to rural development policies for not giving the correct approach for individuals to obtain the set of capabilities and functioning’s associated with the minimum conditions for a worthy life. The land issue is directly linked to income and wealth, but poverty has multiple dimensions that prevent the exercise of basic capabilities, putting people in situations of extreme hardship and deprivation. Public policies should seek the expansion of human capabilities, and if the right to property integrates this list of capabilities, then it must be guaranteed to all.